Evaluation of Prescription Pattern and Rational Prescribing in Eastern Nepal - Chapagain, Kumud; Pokharel, Rais; Paranjape, Bhaskar Diwakar (Journal of Nobel Medical College, 2016)
Background To promote rational prescribing and appropriate use of drugs, it is important to evaluate the prescription pattern using the World Health Organization (WHO) drug use indicators. The aim of this study was to evaluate the prescription patterns and rational prescribing at the private community pharmacies of Biratnagar, Eastern Nepal, using some of the WHO core drug use indicators.Material and Methods Five private community pharmacies were selected using systemic random sampling. Nine hundred patient encounters from these pharmacies were assessed prospectively for four months from September 2015–December 2015. Data was collected from each patient encounter and were recorded directly into a prescription indicator form.Results Average number of drugs prescribed per encounter was 2.14 (n=1930). Percentage of drugs prescribed by generic name and from essential drug list was 45.18% (n=872) and 76.11% (n=1469) respectively. Percentage of encounters in which antibiotic and injection was prescribed were 40.44% (n=364) and 3.44% (n=31) respectively.Conclusion Prescribing practices in Eastern Nepal are not up to the standards recommended by WHO. Drug use evaluation can help to ensure whether the antibiotics are appropriately prescribed or not. Poly-pharmacy, excessive use of antibiotics was quite common and concept of generic prescribing and National Essential Medicine List (NEML) was not appreciable. Standard guidelines should be recommended and strictly followed by the prescribers and National Formulary and NEML should be made available in every health institution. Physicians should be emphasized to prescribe medicines from NEML.Journal of Nobel Medical CollegeVolume 5, Number 1, Issue 8, January-July 2016, 32-36